ANALISA MODEL GETARAN MAIN ENGINE PADA PONDASI MAIN ENGINE KAPAL TANKER 6500 LTDW - Roslyna Lovelylo; Adi Wirawan Husodo; Eky Novianarenti (Proceedings Conference on Marine Engineering and its Application, 2020)
This article mainly describes vibration on new ship’s main engine foundation. The highamplitude of vibration could damage ship’s hull structure and disturb ship’s passenger. The amplitudecan be reduced by adding damping in the main engine foundation. Thereby in this article, modellingthe matemathic equation to get the vibration response. In matemathic equation a software calledMATLAB is used to determine the best graphic response. The stiffness equivalen in the main enginefoundatioon is 1,29 × 106????/????????.In this article use two damping variastion. The first point graphicshow the displacement of main engine foundation in the amount of 0.3 mm on time 0 sec, The secondpoint o graphic show the displacement of main engine foundation in the amount of 0.278 mm on time 0sec, The third point graphic show the displacement of main engine foundation in the amount of 0.299mm on time 0 sec.